Role of tangential biopsy in the diagnosis of nail psoriasis - Laura Bertanha; Ingrid Iara Damas; Rafael Fantelli Stelini; Maria Letícia Cintra; Nilton Di Chiacchio (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Histopathology can be crucial for diagnosis of inflammatory nail diseases. Longitudinal excision and punch biopsies are the most used techniques to obtain the tissue sample. However, there is a low clinical-histopathological correlation, besides the risk of nail dystrophy. Tangential excision biopsy (TB) is a well-established technique for the investigation of longitudinal melanonychia. TB could also be used to evaluate diseases in which histopathological changes are superficial, as in psoriasis. Objective To study the value of TB in the histopathological diagnosis of nail psoriasis. Methods This is a prospective and descriptive study of the clinical-histopathological findings of samples from the nail bed or matrix and nail plate of 13 patients with clinical suspicion of nail psoriasis. Biopsies were obtained through partial nail avulsion and TB. Results In nine patients, the hypothesis of psoriasis was confirmed by histopathology; in one, the criteria for diagnosing nail lichen planus were fulfilled. The tissue sample of only one patient did not reach the dermal papillae, and, in four of 13 patients, the adventitial dermis was not sampled. No patient developed onychodystrophy after the procedure. Study limitations In three patients, the clinical and, consequently, histopathological nail changes were subtle. Also, in one patient's TB didn't sample the dermal papillae. Conclusions TB is a good option to assist in the histopathological diagnosis of nail psoriasis, especially when appropriate clinical elements are combined. Using this technique, larger and thinner samples, short postoperative recovery time, and low risk of onychodystrophy are obtained.